2015
DOI: 10.1590/s1517-838246420131281
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Aspilia latissima (Asteraceae)

Abstract: We evaluated the antimicrobial activity of Aspilia latissima - an abundant plant from the Brazilian Pantanal region - against Candida albicans, Candida parapsilosis, Candida krusei, Candida tropicalis, Pseudomonas aeruginosa, Enterococcus faecalis, Escherichia coli and Staphylococcus aureus. The crude extracts and fractions showed activity in all tested microorganisms. The chloroform fraction of the leaves and roots showed the most antimicrobial activity against S. aureus, with an MIC of 500 μg/mL. This fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The other compounds tested, i.e., 2 , 4 , 6 , 7, 10 , 11 , 14, or 17 , did not exhibit significant cytotoxicity (IC 50 above 100 μM). The lack of cytotoxicity against the two normal cell lines of these diterpenoids is valuable information, considering that some kaurane-type diterpenoids from Aspilia species have showed antibacterial and antifungal effects [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other compounds tested, i.e., 2 , 4 , 6 , 7, 10 , 11 , 14, or 17 , did not exhibit significant cytotoxicity (IC 50 above 100 μM). The lack of cytotoxicity against the two normal cell lines of these diterpenoids is valuable information, considering that some kaurane-type diterpenoids from Aspilia species have showed antibacterial and antifungal effects [5].…”
Section: Resultsmentioning
confidence: 99%
“…Plants from the genus Aspilia (Asteraceae) occur widely in South, South-West, and West Kenya, from the coast to Lake Victoria. The genus Aspilia exhibits biological activities, including antibacterial and antifungal effects, mainly attributed to the presence of kaurane-type diterpenoids [3,5] and sesquiterpene lactones [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a single plant species can exhibit different activity levels (sensitivity) in vitro, depending on the Candida species targeted in tests [27]. Different methodologies have been proposed to determine the antifungal activity of natural products against Candida species [28][29][30], and has been the Disk diffusion the most used. Disk diffusion results showed that almost all crude extracts tested were active against the Candida ATCC strains, C. tropicalis and C. krusei, and seven proved active against C. albicans and C. parapsilosis (▶table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Os extratos de plantas são usados na maneira de agentes convencionais, medicinais e antimicrobianos por ao redor de 6080% da população mundial (KHAN et al, 2018). Assim, com base na indicação de uso popular, extratos vegetais de conhecida atividade antimicrobiana pode ter significado nos tratamentos terapêuticos (SOUZA et al, 2015).…”
Section: Extratos E óLeos Essenciais Como Fonte De Moléculas Para Tra...unclassified